Rancang Bangun Alat Pengasap Tipe Paralel - Gemilang, Tirta Satria; Asmara, Sandi; Tamrin, Tamrin; Warji, Warji (Jurnal Agricultural Biosystem Engineering, 2024)
This research aims to design, manufacture and test a parallel type smoker which has an output that can be controlled and has uniform temperature in each smoker cabinet. In this research, design, assembly, testing and temperature regulation were carried out. This parallel type smoker has 3 main parts, namely the combustion stove, inlet pipe, and smoking cupboard. In the inlet pipe there is a faucet which functions as a control for the smoke output and temperature from the combustion stove to the smoking cupboard. In terms of testing, this tool was tested in several stages, namely trial 1, trial 2, and performance test. After the test is complete, the final stage is carried out, namely equalizing the temperature in each cupboard. The trial phase 1 was carried out with treatment on the operation of the smoke cupboard. Where the stages of operation of all cupboards are carried out simultaneously, then operation of 2 cupboards is carried out and one path is closed alternately. The results showed that the tool experienced problems in the form of unstable temperatures and leaks in the smoker cupboard, so it required patching with silicon. After design improvements have been made, trial 2 and performance testing are continued. Trial 2 was carried out to find out whether the tool still had problems or not before carrying out a performance test. The treatment for trial 2 was the same as that given during trial 1. As a result, the device had no leaks and the temperature was stable and the device was ready to operate at the 15th minute. After that, a performance test was carried out which had the same stages as trials 1 and 2. This is intended to see whether the tool is in accordance with the results during testing or not. After the performance test is carried out, the final stage is to equalize the temperature in each cupboard to produce the same and stable temperature. This equalization is done by adjusting the opening of the faucet valve on the inlet pipe. The results obtained were a parallel type smoker which had 3 smoking cabinets with the same temperature around 37oC. This temperature can used for low smoking temperature.Keywords: Design of Smoker, Parallel, Temperature.